Performance for the commemoration of the 100th anniversary of the 100th anniversary of the birth of Sh.Y.Abramovitsh (Mendele Moykher Sforim)
Performance for the commemoration of the 100th anniversary of the 100th anniversary of the birth of Sh.Y.Abramovitsh (Mendele Moykher Sforim).